Application of Group V Base Oils in the Development of Advanced Engine Oil Formulations (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The continuous evolution of internal combustion engines toward higher efficiency and reduced emissions has necessitated the development of ultra-low viscosity engine oils, such as 0W-16 and 0W-20 grades. While Group III and Group IV (polyalphaolefins or PAOs) base stocks provide excellent foundations for these formulations due to their high viscosity indices and oxidative stability, their non-polar nature introduces critical challenges regarding additive solubility and seal compatibility. Group V base oils, comprising a diverse class of synthetic fluids including esters, polyalkylene glycols (PAGs), and alkylated naphthalenes, have emerged as indispensable high-performance enhancers in modern lubricant chemistry. Rather than serving as the primary bulk fluid, these highly polar synthetic stocks are strategically blended into Group III/IV matrices to resolve inherent physiochemical deficiencies, fundamentally altering the performance profile of the final formulation.This paper presents a comprehensive investigation into the application of Group V base oils for advanced engine oil development, focusing on their mechanisms of action as co-base stocks. By examining their role as additive solvents, particularly in enhancing the dispersancy and stability of polyisobutylene-bis-succinimide (PIBSI) additives, this research highlights how ester-fortified formulations manage high-temperature deposit formation. Furthermore, we propose a structured methodological framework for formulating and evaluating Group V-enhanced lubricants, emphasizing solvency, seal compatibility, and thermal resistance. Through hypothetical evaluation plans and rigorous discussion of practical and ethical deployment considerations, this work provides a foundational roadmap for next-generation engine oil design.